Rice Land Designation Policy in Vietnam and the Implications of Policy Reform for Food Security and Economic Welfare - Giesecke, James A.; Tran, Nhi Hoang; Corong, Erwin L.; Jaffee, Steven (Taylor and Francis, 2013)
With the aim of promoting national food security, the Vietnamese government enforces the designation of around 35 per cent of agricultural land strictly for paddy rice cultivation. We investigate the economic effects of adjusting this policy, using an economy-wide model of Vietnam with detailed modelling of region-specific land use, agricultural activity, poverty and food security measures. Our results show that the removal of the rice land designation policy increases real private consumption by an average of 0.35 per cent per annum over 2011–2030, while also reducing poverty, improving food security and contributing to more nutritionally balanced diets among Vietnamese households.